(untitled) (MCIT: Proceedings of International scientific and practical conference, 2020)
In the people’s lives wireless networks play a big role. It is necessary to understand the basic concept of wireless networks, to consider the security issues related to them, and then observe how they work and what benefits they can bring in different cases. In this regard the given research paper presents the fundamental principles of security as well as related open questions. It reviews the security issues of the wireless networks. Security of protocols of wireless network routing has become an urgent necessity to stimulate the network launching and expand the area of its usage. Therefore, the presented research paper proposes and defines different solutions and concepts for security.